Новый вид трематод рода рипидокотиле - Rhipidocotyle kovalae sp. n. (Trematoda, Bucephalidae) из осетровых рыб Волги - Иванов, В.П. (Вестник зоологии, 1967)
In the intestine of Huso huso L. and Acipenser guldenstadti Brand t. taken from! the river Volga the new species of trematodes belonging to the genus of Rhipidocotyle were found. Diagnosis. The species is similar to Rh. illense (Zigler, 1883) but it differs, mainly in the greater size of its body and the greater size of many organs. The uterus goes far beyond the fore margin of follicles and reaches the sucker, the left vitelloduct goes between the testicles and the rear margin of follicles is in the middle of the body or closer to the back part of the body. In honour of the Ukrainian scientist-trematodologist V. P. Koval, the new species is named Rhipidocotyle (Rh.) kovalae Ivanov V. P. The type Ph. kovalae is kept in the zoological museum of Volgograd Pedagogical Institute.